Landscaping of non-governmental organizations working to improve reproductive, maternal, neonatal, child health and nutrition services in tribal India: a scoping study - Giri, Ashish; Wassey, Abdul; Dogra, Vishal (International Journal Of Community Medicine And Public Health, 2020)
Background: Nearly 104 million (9%) of the total Indian population live in tribal areas. For the tribal population, in the recent past, many organizations initiated health programs. However, there is little understanding of the work they do in the health and nutrition area. In this scoping study, the study aimed to review NGO based models of healthcare delivery with an emphasis on reproductive, maternal health, neonatal and child health, and nutrition (RMNCHN) related interventions in tribal areas of India. Methods: A list of NGOs, in districts having 35% tribal population, was made. NGOs with functional websites, RMNCHN related interventions and registered with the Government of India online portal “NGO darpan” were selected using multistage search criteria. NGO types, their approaches for RMNCHN and intervention models were studied. Results: A total of 1503 NGOs were working on tribal health in 115 districts having >35% tribal population. Out of these, only 103 NGOs had an active health intervention and provided information freely in open public access. Only 36 NGOs had a well-structured program in reproductive, maternal, child health and nutrition area. A compendium of good practices by 12 NGOs working in RMNCHN was prepared. Conclusions: A limited number of NGOs in tribal India works on reproductive, maternal health, neonatal and child health, and nutrition issues. The health-related interventions are primarily at a small scale, community-based, lacks continuum of care and are present in districts with a lesser tribal population.